Prevalence of Cardiac Disease in Asymptomatic Pregnant Females Coming to OPD in Tertiary Care Hospital - Shahid, Aisha; Shah, Nighat Ali; Kashaf, Memoona; Sheerin; Falak, Faiza; Sattar, Ayesha (Indus Journal of Bioscience Research, 2025)
Objective: To determine the prevalence of structural cardiac disease among asymptomatic pregnant females presenting to the antenatal outpatient department of a tertiary care hospital. Study Design: Cross-sectional study. Place and Duration of Study: Department of Obstetrics and Gynecology, Jinnah Postgraduate Medical Centre (JPMC), Karachi; conducted over a period of three months from March, 2025 to May, 2025. Methodology: A total of 119 asymptomatic pregnant women aged 15–45 years attending routine antenatal checkups were enrolled using non-probability consecutive sampling. Women with known cardiac history, symptomatic heart disease, multiple pregnancies, or pregnancy-induced complications were excluded. After informed consent, participants underwent clinical screening, ECG, and if required, transthoracic echocardiography performed by an experienced cardiologist. Data on demographics, medical history, and clinical symptoms were collected using a structured questionnaire. Prevalence of cardiac disease was documented and analyzed using SPSS version 20. Results: Structural cardiac abnormalities were detected in 9 women (7.56%), including rheumatic mitral stenosis (n=3), atrial septal defect (n=2), mitral valve prolapse (n=1), mild pulmonary hypertension (n=1), dilated left atrium with reduced EF 30–50% (n=1), and severe tricuspid regurgitation (n=1). Conclusion: This study demonstrates a notable prevalence of undiagnosed structural cardiac disease among asymptomatic pregnant women. Routine antenatal screening using ECG and echocardiography may play a pivotal role in early diagnosis and prevention of adverse maternal and fetal outcomes, especially in high-risk populations. Incorporating cardiac assessment into antenatal protocols in resource-limited settings should be considered a public health priority.